Economic relations between Turkey and the EU in times of political stalemate - Lukáš Forýtek (World Economy and Policy (WEP), 2022)
Deterioration of Turkey-EU political relations and stalemate in the accession process raise the ques-tion what (if any) impact does it have on economic cooperation. The paper analyses and evaluates data of three crucial pillars of the economic cooperation: The Customs Union, the European Investment Bank loans, and the Pre-accession assistance funds. The findings of the research say that metamorphosis of political relations did not influence the economic collaboration through Customs Union. Turkey's bilateral trade with EU has been stably growing and slumps that occurred were caused by macroeconomic conditions (i.e. world financial crisis). On the other hand, the value of the Turkish projects funded by EIB decreased substantially in 2016 and since 2019 the lending to Turkey has been suspended. Data for pre-accession assistance programs show that allocations to Turkey declined. Moreover, 2021-2027 EU pre-accession assistance program brought higher flexibility that enables EU promptly react on a development in particular country. To conclude, the economic collaboration based on Customs Union seems to be stable with no deeper impact of deterioration of political relations, on the other hand, Turkey has lost access to loans from EIB, and its economic development can be negatively influenced through changes in EU pre-accession assistance programs.
Keywords: 330; Turkey; EU; Customs Union; pre-accession assistance; economic cooperation